Issues of Training the Teachers in Khorezm in the 30s of the XX Century - Xusainbekova Gulchira Mavlonbekovna (International Journal on Integrated Education, 2021)
The article examines the cultural and educational environment of Khorezm during the period of socialist ideology. The contradictions between the methodology of culture and its development are presented.